Monipaikkainen Viipuri : Muistitietotutkimus siirtoväen kaupunkilaisesta karjalaisuudesta - Pietiläinen, Terhi (Helsingin yliopisto, 2025)
This oral history research deals with the reminiscences and urban Karelianness of those who were evacuated from the city of Vyborg and its surrounding areas when it was ceded to the Soviet Union at the end of World War II. I also analyse Vyborg and its inhabitants’ multi-locality and their experiences of war in relation to the hegemonic narrative, which has influenced Karelian culture and the narrative identity of these evacuees to this day. The study is based on data from interviews undertaken over the period 2000–2002 in the From Karelians to resettled Karelians project, which was implemented in cooperation between the Department of Ethnology at the University of Helsinki and the Karelia Association. The interviews included about 330 former residents of the parishes and municipalities of ceded Karelia. Of these, 40 interviews with people who originally hailed from Vyborg were used in the research material. In my data, the persons from Vyborg and its districts were a catalyst for, and a shaper of, the peer community. The interviewees represent a wide range of professions, from ordinary working people to the well-educated. Based on the interviews a picture emerges of how these individuals put their Karelian evacuee identity into words in the early 2000s. The videotaped interviews I undertook were dialogical, semi-structured thematic interviews that combined a biographical approach with the key themes of Karelian evacuee identity. These themes include for example, childhood in a lost home region, experiences as evacuees during the war years of 1939–44 and settling in a new home region in the post-war period, as well as manifestations of Karelian identity. In particular, I paid attention to the dialogic and materialistic nature of the interviewees’ recollections, which manifested itself in many ways, both as concrete and remembered places and as social and material practices of remembrance. I examined the reminiscence narrative from two perspectives: Karelian and urban. I interpret both their individual and ...